Beyond Stigma: Disability Identity in School Contexts - Mueller, Carlyn Oberst (My University, 2019)
This dissertation focuses on adolescent disability identity development and centers the expertise about this phenomenon in the lived experiences of students and adults with disabilities, and a larger context of disability community and culture. The purpose of understanding disability identity is twofold: first, to conceptualize adolescent disability identity development from within educational contexts, and second, to understand the impact of participatory research methods towards this development. To date, the scholarship around disability identity development and adolescents, particularly in the field of special education, has focused on development of social skills for friendships with nondisabled peers (e.g. Zambo, 2010) and negotiation (or attempted negation) of stigma, which is itself due to the overwhelmingly negative social and cultural meanings of the disability label itself (e.g. Kauffman, 2003; Shifrer, 2013). Teachers, themselves frequently nondisabled (Hart & Williams, 2009) attempt to support students academically and socially through this negotiation of stigma, from within their own training and personal experience as a nondisabled student (Linton, 1998). Changing this way of “managing” disability requires a shift in both the conceptual and methodological focus of disability from within the context of special education, and a shift from labeling disability as a feature of a person which must be remediated and normalized. Ware (2002) notes that this shift is “particularly significant in K-12 public schools, where schools reproduce an “understanding of disability warped by the shroud of shame, pity and tragedy in which the disabled students’ needs, deficits, and problems are wrapped- constructing the student’s institutional identity” (p. 152). Instead of assuming this institutional identity as a natural consequence of disability labeling, the study positions disabled students as knowledge holders and experts in their own identities. The first phase of the dissertation involved qualitative interviewing and reflection from disabled adults on their educational experiences and disability awareness in school, which informed and helped identified “levers” of disability identity that have an impact on growth, development, and awareness of each participant’s sense of themselves as members of a disability community. Following the interviews and participation of the disabled adults, the second part of the study involved participation of adolescents with disabilities in a large public high school special education program in the Pacific Northwest. The adolescent participants engaged in both qualitative interviewing about disability identity and a photovoice project where they discussed their identity experiences in school related to disability. Following this phase, the adult participants engaged with the students’ photovoice materials to identify shared experiences and identity resources (Gee, 2003) of disability identity development in school. Common shared disability identity resources included participation in self-contained special education courses and removal from general education; an initial realization of disability and difference; silence around disability in curriculum and from special and general education teachers; and attempts at participation in disability community in mostly online spaces. This study contributes to the theoretical and methodological conversations around adolescent experiences of disability in schools in a few important ways. First, it centers student meaning-making around disability as the major source for both data collection and This is the intolerable cost of special education and related disability research that treats individuals with disabilities as a subject under study and intervention, rather than meaning-makers, capable of creating community and solidarity, negotiating power and stigma, and articulating the changes that need to be made to make their communities more inclusive. Understanding these ideas about identity could potentially lead to developing schools and instructional spaces that support positive disability identity, which could have far-reaching impact on the academic and social experiences of students with disabilities in school.
Thesis (Ed.D.)--University of Washington, 2019
Keywords: adolescent identity; disability identity; special education; Special education; Disability studies; Education - Seattle